Przychody z turystki jako stymulator rozwoju gospodarczego województwa zachodniopomorskiego - Milewski, Dawid (Tourism as a Stimulator of the Westpomerania Province Economic Development, 2005)
The article concerns economic functions of tourism development in Westpomeranian province, Poland. The author estimated the incomes generated by tourism development in the above mentioned province and their regional meaning. Estimated values are compared to Gross output and Gross value added generated by other sectors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 91-96